Pengaruh Gaya Hidup Hangout dan Word of Mouth Terhadap Keputusan Pembelian di Kedai Retjeh Kopi Gondang - Jazilatun Nimah; Hartono Hartono; Rini Armin (Indo-Fintech Intellectuals: Journal of Economics and Business, 2023)
This study aims to determine the influence of the hangout lifestyle and word of mouth on purchasing decisions at the Gondang coffee retjeh shop. This study uses a quantitative method with a total sample of 96 respondents using incidental sampling technique. The data collection method uses an online questionnaire. The results of this study indicate that the hangout lifestyle partially influences purchasing decisions (Sig 0.000 < 0.05, and tcount 5.928 > ttable 1.989) and word of mouth partially influences purchasing decisions (sig 0.000 <0.05 and tcount 4.909 > ttable 1.989). Hangout lifestyle and word of mouth simultaneously influence purchasing decisions at Gondang coffee retjeh shop (sig 0.000 <0.05 and fcount 202,354 > ftable 3.09).